Rice Processing for Export in the Cuu Long Delta Region (Indian Journal of Extension Education, 2012)
The research results showed that capacity of rice plant processing ranged from 30 tonnes to 500 tonnes per day, with an average 170.2 tonnes/day. There were 20 per cent millers who operated over ideal capacity/year, from 130 to 141 per cent. However, most of the millers (80%) operated below ideal capacity/year. The paddy inputs among millers ranged from 6 tonnes to 500 tonnes/day and an average with 136 tonnes/day. The percentage of head rice recovery for brown rice was highest in the winter spring season (ĐX), followed was Autumn-winter season (TĐ) and lastly with Summer-Autumn season (HT), with 73.44 per cent; 71.67 per cent and 68.81 per cent respectively. In case of IR 50404 rice variety, the head rice recovery is highest among other rice varieties so far. This is one of the reasons why this variety is grown in more area even if it is of low quality. The moisture content range of paddy being milled is from 15 per cent to 18 per cent. The ideal moisture content of paddy milled is 16 per cent. The status of rice husk consumption is not stable in the output and beneficial to millers, consumers and environment. The low quality rice varieties such as IR 50404, OM 576, occupied10- 80 per cent of total paddy milled, average with 48 per cent. The varieties with medium quality occupied 35 per cent, while high quality variety was only 20 per cent. The suitable channel for input and output of the millers showed that farmers sold paddy to the traders, and milled paddy into brown rice then sold it to the millers. The millers polished this brown rice and sold to the exporting companies. This channel indicated the high specialization, but it occupied only 33 per cent in the system. The study was also synthetized into11 main constraints, which millers faced in their rice processing activities and 10 important suggestions aimed to improve and develop rice-processing sector for export in the Cuu Long Delta region of Vietnam.